Characteristics of pedagogical change in integrating digital collaborative learning and their sustainability in a school culture: e‐CSAMR framework. (28th January 2021) - Shamir‐Inbal, Tamar; Blau, Ina
Abstract: Collaborative learning is perceived as an important component of Information Communication Technologies (ICT) integration in schools. The purpose of this study was to examine an initiative of the Ministry of Education that promoted intra‐school and inter‐school digital collaborative learning projects. The participants were 159 district ICT leaders, who designed 37 digital collaborative projects containing 73 learning activities to promote inter‐school student interactions. The study was conducted within the qualitative research paradigm through analysis of digital collaborative learning activities. Additionally, the participants were required to share their experiences regarding digital collaboration through an open‐ended online questionnaire. The thematic analysis revealed all four levels of the SAMR model, rating pedagogical changes during technological integration; the most common were the model's two middle levels: Augmentation and Modification. Moreover, we explored the degree of teamwork (information sharing, cooperation, or collaboration), complexity of collaboration (intra‐school vs. inter‐school) and sustainability of collaborative learning within the school culture. Most of the activities reflected the cooperation level of teamwork, while in the highest level—collaboration was less common. Surprisingly, complexity of collaboration and its sustainability in school culture were negatively interconnected. Regarding the extent of collaboration, some activities were categorized as "Islands of innovation, " the majority were comprehensive and conducted on the organizational level, while only few involved the wider community‐parents or other stakeholders. Based on the bottom‐up analysis of pedagogical changes in digital collaboration activities, we suggested a comprehensive e‐CSAMR framework. The implications for educational theory and practice are discussed. Lay Description: What is already known about this topic?: Collaborative learning is an important component of ICT integration in schools and can be conducted in the form of within‐school and between‐school digital collaborative learning projects. SAMR model rates four levels of pedagogical change in ICT integration as either minor— Substitution and Augmentation, or substantial changes— Modification and Redefinition . What this paper adds?: We explored the degree of teamwork (information sharing/cooperation/collaboration), its complexity (within‐school/between‐school) and its sustainability in the school culture. The thematic analysis of e‐collaborative projects and teachers' reports revealed all levels of SAMR, while the most common were the model's two middle levels: Augmentation and Modification . Most of the activities reflected the cooperation level of teamwork, while in the highest level—collaboration was less common. Surprisingly, complexity of collaboration (within‐school/between‐school) and its sustainability in school culture were negatively interconnected. Regarding the extent of collaboration, some activities were " Islands of innovation, " the majority were conducted on the organizational level, while only few involved parents or other stakeholders. Implications for practice and/or policy: Based on the bottom–up results, we suggested a comprehensive e‐CSAMR framework, which can be used by educators and policy‐makers for analysis of pedagogical changes in e‐collaboration. In between‐school collaboration, educators search for schools that share common parameters with them such as residential area, region, ethnicity, language and religion, students of the same age.